Pengaruh Kompetensi Aparat Desa, Pemanfaatan Teknologi Informasi dan Sistem Pengendalian Internal Terhadap Akuntabilitas Pengelolaan Dana Desa - Nela Safelia (Magister Ilmu Akuntansi Universitas Jambi, 2023)
This study aims to see the influence of village apparatus competence, the use of information technology and internal control systems that can affect the accountability of managing village funds in Maro Sebo Ilir District, Batang Hari Regency. This research is a descriptive quantitative research, the type of data used in this research is primary data, from the results of distributing questionnaires and secondary data obtained from library research and documents related to village fund management. The population and sample used in this study were all village fund managers, while the data analysis technique in this study used multiple linear regression analysis. The results of the study show that the competency of the village apparatus, the internal control system has an effect on the accountability of village fund management, while the use of information technology has no effect on the accountability of village fund management.